Molecular and parasitological survey of trypanosomosis in KwaZulu-Natal and the development of cathepsin L-like real-time PCR assays for parasite discrimination - Neves, Luís C.B.G. (University of Pretoria, 2022)
Dissertation (MSc (Veterinary Science Tropical Diseases))--University of Pretoria, 2020.